Multinational prospective cohort study over 18 years of the risk factors for ventilator-associated pneumonia in 9 Asian countries: INICC findings - Rosenthal, Victor Daniel; Yin, Ruijie; Rodrigues, Camilla; Myatra, Sheila Nainan; Divatia, Jigeeshu Vasishth; Biswas, Sanjay K; Shrivastava, Anjana Mahesh; Kharbanda, Mohit; Nag, Bikas; Mehta, Yatin; Sarma, Smita; Todi, Subhash Kumar; et al. (American journal of infection control, 2023)
•Prospective cohort study of risk factors for VAP over 18 years in 9 Asian countries.•Male gender, age, public and private hospitals increase the risk of VAP.•Medical-Surgical, neurologic, and medical ICUs showed the highest risk for VAP.•Device utilization and length of stay increase significantly the risk of VAP.•It is recommended limiting use of tracheostomy. Ventilator associated pneumonia (VAP) rates in Asia are several times above those of US. The objective of this study is to identify VAP risk factors. We conducted a prospective cohort study, between March 27, 2004 and November 2, 2022, in 279 ICUs of 95 hospitals in 44 cities in 9 Asian countries (China, India, Malaysia, Mongolia, Nepal, Pakistan, Philippines, Sri Lanka, Thailand, Vietnam). 153,717 patients, followed during 892,996 patient-days, acquired 3,369 VAPs. We analyzed 10 independent variables. Using multiple logistic regression we identified following independent VAP RFs= Age, rising VAP risk 1% per year (aOR=1.01; 95%CI=1.00-1.01, P<.0001); male gender (OR=1.17; 95%CI=1.08-1.26, P<.0001); length of stay, rising VAP risk 7% daily (aOR=1.07; 95%CI=1.06-1.07, P<.0001); mechanical ventilation (MV) device utilization (DU) ratio (OR=1.43; 95%CI=1.36-1.51; p<.0001); tracheostomy connected to a MV (OR=11.17; 95%CI=9.55-14.27; p<.0001); public (OR=1.84; 95%CI=1.49-2.26, P<.0001), and private (OR=1.57; 95%CI=1.29-1.91, P<.0001) compared with teaching hospitals; upper-middle income country (OR=1.86; 95%CI=1.63-2.14, P<.0001). Regarding ICUs, Medical-Surgical (OR=4.61; 95%CI=3.43-6.17; P<.0001), Neurologic (OR=3.76; 95%CI=2.43-5.82; P<.0001), Medical (OR=2.78; 95%CI=2.04-3.79; P<.0001), and Neuro-Surgical (OR=2.33; 95%CI=1.61-3.92; P<.0001) showed the highest risk. Some identified VAP RFs are unlikely to change= age, gender, ICU type, facility ownership, country income level. Based on our results, we recommend limit use of tracheostomy, reducing LOS, reducing the MV/DU ratio, and implementing an evidence-based set of VAP prevention recommendations.